Індіанці поселення Акома в Нью-Мексико - Боряк, О. (Народна творчість та етнографія, 2005)
Acoma Pueblo, sometimes known as "Sky City," is probably the oldest continuously inhabited town in the central part of the state New Mexico in the United States. Acoma has been inhabited since the 12th century. The town is dramatically located on a sandstone mesa. The article describes a creation of the Indian's settlement, struggle with Spaniards and cultural consequences of coexistence with Europeans. It illustrates problems of Pueblo Indians life, their main economic and household activity, building and pottery in particular. The author discusses the huge ancient mission San Esteban del Rey (St. Stephen) church, founded by the Spanish Franciscan missionaries in 1626 on the mesa top.